Infection risk in autoimmune hematological disorders with low‐dose rituximab treatment - Wang, Honglei (J Clin Lab Anal, 2020)
BACKGROUND: Rituximab has been widely used in many autoimmune diseases. AIM: To evaluate the infection risk of rituximab in autoimmune hematological disorders. METHODS: Retrospectively studied and compared the clinical data of 89 patients in our hospital who used low‐dose rituximab (group R) or pulse cyclophosphamide (group C) for their refractory/relapsed autoimmune hematological diseases from January 2011 to January 2017. The kinds of their diseases included autoimmune hemolytic disease (AIHA), Evans syndrome, and idiopathic thrombocytopenic purpura (ITP). All patients chose either rituximab treatment or cyclophosphamide treatment on their own considerations. FINDINGS: The median follow‐up time was six months in group R and four months in group C. After treatments, the patients in group R showed higher white blood cell (WBC) count and neutrophil count than group C (P = .020, P = .037). CD20‐positive B cells in group R remained at a very low level after rituximab treatment and need about 15 months to return to normal level, which was longer than group C (six months). The incidence of infection in these two groups has no significant difference, which was 34.7% (17/30) in group R and 32.5% (13/28) in group C (P = .976). Tuberculosis infections after rituximab treatment were found in three patients for the first time. CONCLUSION: The G‐CSF, nadir WBC count, and IgA level were protective factors of infection during rituximab treatment. Low‐dose rituximab therapy in autoimmune hematological diseases does not increase infection risk compared with cyclophosphamide.